Pharmacogenetic information for patients on drug labels - Haga SB; Mills R; Moaddeb J (Dove Medical Press, 2014)
Susanne B Haga, Rachel Mills, Jivan Moaddeb Center for Applied Genomics and Precision Medicine, Department of Medicine, Duke University, Durham, NC, USA Abstract: Advances in pharmacogenetic research have improved our understanding of adverse drug responses and have led to the development of pharmacogenetic tests and targeted drugs. However, the extent of the communication process and provision of information to patients about pharmacogenetics is unclear. Pharmacogenetic information may be included in sections of a drug's package insert intended for patients, which is provided directly to patients or communicated via the health provider. To determine what pharmacogenetic information, if any, is included in patient-targeted sections of the drug label, we reviewed the labels listed in the US Food and Drug Administration's Table of Pharmacogenomic Biomarkers in Drug Labels. To date, 140 drugs include pharmacogenetic-related information in the approved label. Our analysis revealed that pharmacogenetic information is included in patient-targeted sections for a minority (n=29; 21%) of drug labels, with no obvious pattern associated with the inclusion of pharmacogenetic information. Therefore, patients are unlikely to learn about pharmacogenetics through written materials dispensed with the drug. Given that there are also inconsistencies with regard to inclusion of pharmacogenetic information in the patient counseling information section, it is also unlikely that patients are receiving adequate pharmacogenetic information from their provider. The inconsistent presence of pharmacogenetic information in patient-targeted sections of drug labels suggests a need to review the criteria for inclusion of information in patient-targeted sections in order to increase consistency and patient knowledge of pharmacogenetic information. Keywords: pharmacogenomics, pharmacogenetics, US Food and Drug Administration, drug safety, patient education